Estimating Bilateral Exposures in the German Interbank Market: Is there a Danger of Contagion? - Christian Upper; Andreas Worms (Deutsche Bundesbank, 2002)
Credit risk associated with interbank lending may lead to domino effects, where the failure of one bank results in the failure of other banks not directly affected by the initial shock. Recent work in economic theory shows that this risk of contagion depends on the precise pattern of interbank linkages. We use balance sheet information to estimate the matrix of bilateral credit relationships for the German banking system and test whether the breakdown of a single bank can lead to contagion. We find that the financial safety net (institutional guarantees for saving banks and cooperative banks) considerably reduces - but does not eliminate - the danger of contagion. Even so, the failure of a single bank could lead to the breakdown of up to 15 % of the banking system in terms of assets. – – Kreditrisiken aus Interbankbeziehungen können zu Dominoeffekten führen indem der Zusammenbruch einer Bank den Zusammenbruch anderer Banken bewirkt, die nicht direkt vom ursprünglichen Schock betroffen waren. Neuere theoretische Arbeiten zeigen, dass dieses Ansteckungsrisiko von der genauen Struktur der Interbankbeziehungen abhängt. Wir schätzen die Matrix bilateraler Kreditbeziehungen für das deutsche Bankensystem auf Basis von Bankbilanzdaten und testen anschliessend, ob der Zusammenbruch einer einzelnen Bank zu Ansteckungseffekten führen kann. Wir kommen zu dem Ergebnis, dass die Sicherungssysteme (institutionelle Garantien für Sparkassen und Kreditgenossenschaften) die Ansteckungsgefahr zwar beträchtlich verringern aber nicht vollständig eliminieren können. Die Zusammenbruch einer einzelnen Bank kann trotzdem zu einem Verlust von 15 % der Aktiva des gesamten Bankensystems führen.
Keywords: G28; G21; 330; contagion; interbank market; regulation of banks; Geldmarkt; Kreditrisiko; Bankenkrise; Schätzung; Deutschland